ENT 530 Social Media Portfolio / Alia Nur Hazirah Amirudin - Amirudin, Alia Nur Hazirah (2019)
The assignment is the study on how to run a business by using the social media. I have chosen a business to be run by me which is a business of selling scarves for women. By doing this business, I have learned on how to promote our products by using social media which is Facebook. Facebook is a social networking and e-commerce site that makes it a strategic platform for entrepreneurs to market their products/services. While doing this assignment, I have learned on how to create sale postings by using teaser, soft sell and hard sell. Actually, an entrepreneur has to be proficient when closing sales using effective "soft sell" to answers customers' enquiries. Furthermore, I have learned on how to attract our customers and introduce our product to the customers. We need to set our customers target in order to make sure that our business running smoothly. We must know what customers want. We also need to know how to handle the upcoming problems.